Macroeconomics : theory and policy - Agarwal, Vanita (Dorling Kindersley, 2010)
Macroeconomics: Theory and Policy provides students with comprehensive coverage of all the essential concepts of macroeconomics. A balanced approach between theoretical and mathematical aspects of the subject has been adopted to ensure ease and clarity in learning. The book brings classroom teaching directly to the student with the friendly language that it uses. The purpose behind this book is not only to make the study of macroeconomics simple for the students but to enable them to apply it to everyday situations and the prevailing economic state of affairs. The wide coverage of topics has been designed for use in courses on macroeconomics at the undergraduate level of Indian universities.